EUROPEAN ADVERTISING STRATEGIES - Rijkens Rein (Cassell, 1992)
AFTER EIGHT APPLE COMPUTER UNILEVER'S CAPTAIN ANGE OF FROZEN PRODUCTS CLUB MEDITERRANEE COLGATE TOOTHPASTE KLM ROYAL DUTCH AIRLINE LEVI'S LUX TOILET SOAP MARLBORO MARTINI & ROSSI
AFTER EIGHT APPLE COMPUTER UNILEVER'S CAPTAIN ANGE OF FROZEN PRODUCTS CLUB MEDITERRANEE COLGATE TOOTHPASTE KLM ROYAL DUTCH AIRLINE LEVI'S LUX TOILET SOAP MARLBORO MARTINI & ROSSI